Myths in peritoneal dialysis. Issue 6 (November 2016) - Lee, Martin B.; Bargman, Joanne M.
Abstract : Purpose of review: To clarify misconceptions about the feasibility and risks of peritoneal dialysis that unnecessarily limit peritoneal dialysis uptake or continuation in patients for whom peritoneal dialysis is the preferred dialysis modality. The inappropriate choice of haemodialysis as a result of these misconceptions contributes to low peritoneal dialysis penetrance, increases transfer from peritoneal dialysis to haemodialysis, increases expenditure on haemodialysis and compromises quality of life for these patients. Recent findings: Peritoneal dialysis is an excellent renal replacement modality that is simple, cost-effective and provides comparable clinical outcomes to conventional in-centre haemodialysis. Unfortunately, many patients are deemed unsuitable to start or continue peritoneal dialysis because of false or inaccurate beliefs about peritoneal dialysis. Here, we examine some of these 'myths' and critically review the evidence for and against each of them. We review the feasibility and risk of peritoneal dialysis in patients with prior surgery, ostomies, obesity and mesh hernia repairs. We examine the fear of mediastinitis with peritoneal dialysis after coronary artery bypass graft surgery and the belief that the use of hypertonic glucose dialysate causes peritoneal membrane failure. Summary: By clarifying common myths about peritoneal dialysis, we hope to reduce overly cautious practices surrounding this therapy.